The WHO AFRO external quality assessment programme (EQAP): Linking laboratory networks through EQA programmes - Debrah I. Boeras; Rosanna W. Peeling; Philip Onyebujoh; Ali A. Yahaya; Hieronyma N. Gumede-Moeletsi; Jean B. Ndihokubwayo (AOSIS, 2016)
External Quality Assessment (EQA) surveys performed by the World Health Organization Regional Office for Africa (WHO AFRO) revealed the need for the strengthening of publichealth microbiology laboratories, particularly for testing of epidemic-prone diseases in theAfrican Region. These surveys revealed common issues such as supply chain managementskilled personnel, logistical support and overall lack of quality standards. For sustainableimprovements to health systems as well as global health security, deficiencies identified needto be actively corrected through robust quality assurance programmes and implementation oflaboratory quality management systems. Given all the pathogens of public health importance, an external quality assessment programmewith a focus on vaccine-preventable diseases and emerging and re-emerging dangerouspathogens is important, and should not be stand-alone, but integrated within laboratorynetworks as seen in polio, measles, yellow fever and rubella. In 2015, WHO AFRO collaborated with the US Centers for Disease Control and Preventionthe London School of Hygiene & Tropical Medicine and partners in a series of consultationswith countries and national and regional EQA providers for the development of qualityassurance models to support HIV point-of-care testing and monitoring. These consultationsrevealed similar challenges as seen in the WHO AFRO surveys. WHO AFRO brought forthits experience in implementing quality standards for health programmes, and also openeddiscussions on how lessons learned through such established programmes can be utilised tosupporting and strengthening the introduction of early infant diagnosis of HIV and viralload point-of-care testing. An optimised external quality assessment programme will impact the ability of countries tomeet core capacities, providing improved quality management systems, improving theconfidence of diagnostic network services in Africa, and including capacities to detect eventsof international public health importance.